O movimento criacionista e sua hermenêutica: possibilidades de diálogo entre a teologia e a ciência evolucionista - Garros, Tiago Valentim (2014)
This work explores themes related to the creationist movement and its tense relationship with the theory of biological evolution of Charles Darwin, starting from the widespread notion that the concepts of creation and evolution are mutually incompatible. The work aims at reviewing the specialized bibliography in order to investigate if such dichotomy is necessary and/or epistemologically mandatory, that is, whether or not theism or Christianity lead to an obligatory rejection of the theory of evolution, making evident a real conflict between science and religion. To accomplish that, the study begins with a characterization of the different creationist and evolutionist positions and with a brief historical background of the creationist movement up to these days. In the second chapter, we explore the creationist manner of hermeneutically understanding the book of Genesis, trying to point out the obstacles that make this particular view to be in conflict with science. Then, we analyze what theology, through its hermeneutical efforts, has to say about Genesis, and what the research reveals about the understanding of the Cosmos of the people who wrote the first book of the Bible. Finally, in the third chapter, we analyze the forms of relationship that have been suggested to approach the science/religion controversy and what interaction bridges can be established between theology and evolutionary science from this discussion. We conclude by indicating the path we believe to be the most fruitful for overcoming the notion of conflict between the two fields. This path includes the recognition of the theological, and not scientific, nature of the creation account, the necessary separation between physics and metaphysics when analyzing any finding of modern science and the rediscovery of the doctrine of creation.